FRI0301 Serum exosomes involved in the progression of lupus nephritis. (12th June 2018) - Zhang, Z.; Xue, W.; Ji, J.; Fu, T.; Yang, J.; Gu, Z.
Abstract : Background: Systemic lupus erythematosus (SLE is a chronic autoimmune disease that systemically affects several important organs[. 1 Lupus nephritis (LN is one of the most severe complications of SLE[. 2 Exosomes are important mediators of biological information and play a part in the occurrence and development of various diseases including LN[. 3 Objectives: The aim of study was to find whether exosomes participate in the pathogenesis of lupus nephritis. Methods: We studied 10 patients with SLE but no LN, 10 patients with LN and 10 healthy people which are in line with the SLE classification criteria of American College of Rheumatology diagnostic (ACR) in 1997 and the LN pathological classification of ISN and RPS in 2003. Exosomes were isolated from the serum by ultracentrifugation and confirmed by transmission electron microscope and western blot. The internalisation of exosomes was detected by immunofluorescence Then exosomes were injected into MRL/lpr mouse via the tail vein and co-cultured with mesangial cells. Flow cytometry was used to detect the alteration of cell cycle. The cell proliferation was determined by CCK-8 assay. The inflammatory cytokines (TNF-α, IL-6) and collagen I level in medium supernatant by ELISA, signal pathway by immunoblotting. Additionally, High-throughput sequencing was used to detect the expression of miRNAs in exosomes. Results: The proteinuria and the percent of kidney crescent formation index of LN group was significantly high than oher three groups. Exosomes can be absorbed by mesangial cells quickly. The secrection of inflammatory cytokines and collagen Iof LN group were higher than NLN and control group(p<0.05).PI3K/AKT pathway are involved, But there was no significant difference between NLN group and control group. High-throughput sequencing revealed 11 up-regulated miRNA in SLE relative LN, 3 up-regulated miRNA in LN relative healthy people. Conclusions: LN exosomes can enhance the proliferation and secrection of mesangial cells in which PI3K/AKT pathway is actived. This tip us exosomes may involve in the pathogenesis of LN. References: [1] Shen B, Tan W, Feng G, He Y, Liu J, Chen W, Huang X, Da Z, Xu X, Liu H, Gu Z. The correlations of disease activity, socioeconomic status, quality of life, and depression/anxiety in Chinese patients with systemic lupus erythematosus. Clinical & developmental immunology2013;270878. [2] Chafin CB, Reilly CM. MicroRNAs implicated in the immunopathogenesis of lupus nephritis. Clinical & developmental immunology2013;430239. [3] Abels ER, Breakefield XO. Introduction to Extracellular Vesicles: Biogenesis, RNA Cargo Selection, Content, Release, and Uptake. Cellular and molecular neurobiology2016. Acknowledgements: The Natural Science Foundation of China under Grant (81202368), The Natural Science Foundation of China under Grant (81471603) Disclosure of Interest: None declared